Heterotic Patterns Among Ten Pearl Millet Populations - Dutt, Yagya; Baniwal, C R (Annals of Arid Zone, 2016)
Ten pearl millet [Pennisetum glaucum (L.) R.BR. Emend Stuntz] populationswere evaluated following diallel mating design (excluding reciprocals) for determiningthe heterotic patterns among the ten populations and their crosses, and partitioningof heterosis into average heterosis, variety heterosis, specific heterosis, and furtherto identify base populations for intra- and inter-population improvement programme.In heterotic patterns, average heterosis is more important for characters, namely,grain yield and day to 50% flowering, and specific heterosis has a major rolein IDOO-grain weight. In the present investigation, the heterotic patterns indicatedthat the populations RVPT 93 (102) and crosses HTP88 x HMP9102 x RVPT93(102), RVPT93(102) x ICMV94774 and HP8601 x ICMV95778 can be successfullyexploited as base material for development of inbred lines for hybrids and to developimproved population varieties.